A new era for the defense industry? Security policy and defense capability after the Russian invasion of Ukraine - Klaus-Heiner Röhl; Hubertus Bardt; Barbara Engels (Institut der deutschen Wirtschaft (IW), 2023)
The Russian attack on Ukraine has brought the question of the German Armed Forces' operational capability back into focus. National defense, which seemed to play only a minor role with the end of the Cold War and the dissolution of the Warsaw Pact and the Soviet Union in 1991, now has gained a higher political priority again. In his government declaration of 27 February 2022, German Chancellor Olaf Scholz spoke of a turning point in time due to this war and announced a special fund of 100 billion euros to strengthen the country's defense capabilities. However, these extensive funds can only have a sustainable effect on security policy if the possibilities of the defense industry to supply new weapons systems and the possibilities of the Bundeswehr to use and maintain these weapons are brought into line. In 2020, the approximately 55,500 employees in the defense industrial sector in Germany produced weapons, combat aircraft, warships and military vehicles for approximately 11.3 billion euros; both figures were lower than in 2015 despite Russia's occupation of Crimea in 2014. This policy paper therefore presents the status of plans to strengthen the Bundeswehr and classifies them in terms of security policy. In addition, the German defense industry with its sectors of aircraft and spacecraft, naval shipbuilding, combat vehicles as well as weapons and ammunition is portrayed and the increasingly important area of cyber defense is discussed. The policy paper concludes with defense policy and defense industry recommendations derived from the previous chapters. Recommendations include a long-term plan for strengthening the Bundeswehr and the German defense industry, stronger cooperation with European partner countries on defense projects to reduce dependency on the U.S. and including the defense industry in the European taxonomy for the financial sector, as its current status of non-sustainability threatens especially smaller and medium defense companies that are important for European security. – – Durch den russischen Angriff auf die Ukraine ist die Frage der Einsatzfähigkeit der Bundeswehr erneut in den Fokus gerückt. Die Landesverteidigung, die mit dem Ende des Kalten Krieges und der Auflösung von Warschauer Pakt und Sowjetunion 1991 nur noch eine geringe Rolle zu spielen schien, besitzt nun wieder einen hohen politischen Stellenwert. Bundeskanzler Olaf Scholz sprach in seiner Regierungserklärung vom 27. Februar 2022 von einer Zeitenwende durch diesen Krieg und kündigte ein 100 Milliarden Euro umfassendes Sondervermögen zur Stärkung der Verteidigungsfähigkeit an. Diese umfangreichen Mittel können jedoch nur nachhaltig sicherheitspolitisch wirksam werden, wenn die Möglichkeiten der Industrie zur Lieferung neuer Waffensysteme und die Möglichkeiten der Bundeswehr zur Nutzung und Instandhaltung dieser Waffen in Einklang gebracht werden. Im Jahr 2020 stellten die etwa 55.500 Beschäftigten im verteidigungsindustriellen Bereich in Deutschland Waffen, Kampfflugzeuge, Kriegsschiffe und Militärfahrzeuge für circa 11,3 Milliarden Euro her; beide Werte lagen trotz der bereits erfolgten Besetzung der Krim durch Russland niedriger als 2015. Dieses Policy Paper stellt deshalb den Stand der Pläne zur Stärkung der Bundeswehr vor und ordnet sie sicherheitspolitisch ein. Zudem wird die deutsche Verteidigungsindustrie mit ihren Sektoren Luft- und Raumfahrzeuge, Marineschiffbau, Kampffahrzeuge sowie Waffen und Munition portraitiert und anschließend auf den immer bedeutenderen Bereich der Cyberabwehr eingegangen. Das Policy Paper schließt mit einem Fazit und verteidigungspolitischen und verteidigungsindustriellen Empfehlungen. Zu den Empfehlungen zählt eine Verstetigung der erhöhten Verteidigungsausgaben bei zwei Prozent der Wirtschaftsleistung, um Planungssicherheit für Rüstungsprojekte über 2025 hinaus zu erreichen und die Fähigkeiten der deutschen Verteidigungsindustrie nachhaltig zu sichern, eine verstärkte Kooperation mit europäischen Partnern in der Verteidigungspolitik und in Rüstungsprojekten sowie eine Berücksichtigung des Verteidigungssektors in den Nachhaltigkeitskriterien der Taxonomie für den europäischen Finanzsektor.
Keywords: H12; L64; L88; Z0; 330; Rüstungsindustrie; Rüstungspolitik; Militärausgaben; Deutschland; EU-Staaten